Modernization of “Transport” As Public Transportation to Reduce Personal Vehicle Ownership in the City of Tanjungpinang - Purwasih, Hari Dewi; Sidabutar, Yuanita FD; Suciati, Herlina; Fauzan, Fauzan (Graduate Program Magister Manajemen Pendidikan, 2023)
The Riau Archipelago, which consists of islands, has its own challenges in terms of infrastructure and transportation development, so that the development and growth of each region is not the same, namely with five regencies and two municipalities. The Riau Archipelago has high potential in its tourism sector because each island has its own beauty and exoticism. Tanjungpinang City as the Capital of the Province in the past decade has begun to develop and organize itself to be better in regional order but not yet in its transportation system. Public transportation has not been felt as a very important thing because people can still walk freely by using their private vehicles. Public transportation is still not a matter of urgency in the next decade. This research is a descriptive research, descriptive research is a type of research whose purpose is to present a complete picture of a social setting or is intended to explore and clarify a phenomenon or social reality, by describing a number of variables related to the problem and units studied among the phenomena being tested. Here it will be explained based on a study of the factual conditions of transportation in Tanjungpinang City and their relevance in the next decade.